The Myths of Hades in Plato. An Ethical Reading - Mejía Mosquera, Juan Fernando (Estudios de Filosofía, 2002)
From a distinction between the criticism of the traditional myth, which may lead to its pedagogic use once it is reformed, and the use of the myth in a philosophical research as a tool of thought, this paper proceeds to consider three philosophical myths and establish the way they may be read adequately, specially attempting to establish the ethic-related repercussions that they have in Plato’s work. First, some general considerations regarding the place for myth in Plato’s Philosophy are made. Here in after, a comment of the three myths is made; finally, two types of conclusions are formulated: methodological and ethical.